PERAN PROFITABILITAS DAN LAVERAGE DALAM MEMPENGARUHI NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN SEKTOR HEALTHCARE YANG TERDAFTAR DI BEI PERIODE 2020-2023 - Nisakh, Nur Ainun; Sari, Lita Permata; Minullah, Minullah (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of profitability and Laverage on firm value, as well as the role of dividend policy as a moderating variable. The analysis method employs path analysis with hypothesis testing based on Original Sample values, T-Statistics, and P-Values. The results indicate that: (1) Profitability has a positive and significant effect on firm value (β = 0.795; p = 0.007), supporting the increase in firm value alongside rising profits; (2) Laverage has a negative and insignificant effect on firm value (β = -0.171; p = 0.275), indicating that debt structure does not automatically enhance firm value; (3) Dividend policy strengthens the effect of profitability on firm value (β = 0.504; p = 0.001), confirming its role as a positive moderator; (4) Dividend policy also positively and significantly moderates the effect of Laverage on firm value (β = 0.464; p = 0.022), even though Laverage itself is insignificant. These findings partially align with previous research, such as Zhafira and Tristriarini (2024), but contradict Hanifah (2020) regarding the impact of Laverage. The study emphasizes the importance of dividend policy in optimizing the effects of profitability and Laverage on firm value.